The Effect Of Topical Robusta Coffee Extract (Coffea Robusta) In Accelerating The Healing Process Of Cuts In The Backs Of White Wistar Rats (Rattus Norvegicus) - Aditya Wardhana; Xavier Ongko, Nicolas; Samin, Buter; Diana Putri, Lenni (Jurnal EduHealth, 2023)
The purpose of this study was to test the research hypothesis, namely whether topical administration of coffee extract affects the acceleration of the healing process of cuts on the backs of rats. Based on the results of the research that has been done, it can be concluded that the administration of the Robusta coffee extract (Coffea Robusta) can accelerate the healing of cuts in white Wistar rats, which is characterized by an average difference in the percentage of the recovery. However, after the T-test, the results obtained for H0 were rejected, meaning there was no significant difference between the control group, which was only given 0.9% NaCl and the treatment group, which was given Robusta coffee extract. Topical can accelerate wound healing. The results of this study are expected to be suggestions and references for other researchers who wish to study the use of Robusta coffee extract in understanding the healing process of cuts.